A Rare Site of Ischemic Stroke: Bilateral Corpus Callosum Infarction - Karakaptan, Yasemin; Darıcı, Didem; Demir, Serkan; Çetin, Özdem Ertürk (Cerrahpaşa Medical Journal, 2023)
Cite this article as: Karakaptan Y, Darıcı D, Demir S, Ertürk Çetin Ö. A rare site of ischemic stroke: Bilateral corpus callosum infarction. Cerrahpaşa Med J. 2023;47(3):337-339.